Effectiveness of Content Marketing in Attracting Generation Z Consumer Loyalty - Johni Eka Putra; Nuraida Wahyu Sulistyani; Fahad Ramadhan; Hilman Hidayat (Oikonomia : Journal of Management Economics and Accounting, 2025)
Generation Z has unique characteristics in information consumption and decision-making, especially in the context of digital marketing. They prefer authentic, interactive, and social value-based content over conventional advertising. With the dominance of platforms such as TikTok, Instagram Reels, and YouTube Shorts, an effective marketing strategy should focus on storytelling, user-generated content (UGC), and collaboration with influencers to build deeper engagement. This research uses a qualitative approach with a case study method to analyze successful content marketing strategies in attracting the attention and building loyalty of Generation Z. The data was collected through in-depth interviews with 20 individuals. Data was collected through in-depth interviews with 20 Generation Z individuals and 10 digital marketing practitioners, as well as digital observation of several brands that have successfully adopted content-based marketing strategies. Thematic analysis was conducted to identify interaction patterns and audience preferences for different types of content. The results show that successful digital marketing for Generation Z depends on utilizing the right platform, brand transparency, and data-driven engagement measurement. With an appropriate strategy, companies can increase customer loyalty and strengthen emotional connections with audiences in an increasingly competitive digital era.